2021
DOI: 10.1371/journal.pgen.1009323
|View full text |Cite
|
Sign up to set email alerts
|

Actionable pharmacogenetic variants in Hong Kong Chinese exome sequencing data and projected prescription impact in the Hong Kong population

Abstract: Preemptive pharmacogenetic testing has the potential to improve drug dosing by providing point-of-care patient genotype information. Nonetheless, its implementation in the Chinese population is limited by the lack of population-wide data. In this study, secondary analysis of exome sequencing data was conducted to study pharmacogenomics in 1116 Hong Kong Chinese. We aimed to identify the spectrum of actionable pharmacogenetic variants and rare, predicted deleterious variants that are potentially actionable in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…Owing to the increasing need to gather genetic data for population-wide studies, Yu et al. recently analyzed the WES data of 1,116 Hong Kong samples and identified a set of variants for potential pharmacogenetic use in Hong Kong ( 15 ). Most of their variant data, however, are not publicly available.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the increasing need to gather genetic data for population-wide studies, Yu et al. recently analyzed the WES data of 1,116 Hong Kong samples and identified a set of variants for potential pharmacogenetic use in Hong Kong ( 15 ). Most of their variant data, however, are not publicly available.…”
Section: Introductionmentioning
confidence: 99%
“…PK findings from clinical studies can lead to improvements in therapeutic outcomes through amendments to clinical protocols [ 5 , 15 ] or the development of clinical decision support tools [ 16 ]. It was recently shown that >90% of persons have an actionable drug-gene polymorphism [ 17 , 18 ]. A plethora of clinical studies have been including pharmacogenetics in an effort to describe more of the variability in MTX PK and improve therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating rare genetic variants into pre-emptive pharmacogenetic tests will allow genotyping to be highly effective for a true individualization of patients' drug treatment regimens (33). Besides understanding which drug would fully benefi t from a pharmacogene characterization at the sequencing level, population-specifi c patterns of rare variants should be known (34,35) and taken into consideration for developing population-adjusted genetic profi ling strategies (2,36,37). For instance, CPIC guidelines recommended TPMT and NUDT15 genotyping of common variants for thiopurine dosing.…”
Section: Role Of Rare Variants In Improving the Sensitivity Of Pharmacogenetic Testsmentioning
confidence: 99%
“…In other populations, such as in the Europeans, the characterization of variants in TPMT should be a priority (39). Cost-effectiveness of the analysis of rare variants in pharmacogenes has still to be clearly estimated, however NGS costs have been consistently reducing in recent years and this approach is promising for the future pharmacogenomic analysis (36).…”
Section: Role Of Rare Variants In Improving the Sensitivity Of Pharmacogenetic Testsmentioning
confidence: 99%